Making the Most of Offshore Wind. Re-Evaluating the Potential of Offshore Wind in the German North Sea. - (:unkn) unknown (My University, 2020)
As part of its European Green Deal, the European Commission has announced to present a strategy on offshore wind in 2020. Such a strategy is urgently needed as reaching a climate-neutral Europe will require a massive expansion of offshore wind energy. This raises the question whether energy models used today by wind farm planners and investors can adequately capture the interaction effects between turbines stemming from very large areas covered with offshore wind farms at high installed capacity density. To better understand such effects, Agora Energiewende and Agora Verkehrswende commissioned the Department of Wind Energy at the Technical University of Denmark as well as the Max-Planck-Institute for Biogeochemistry to simulate future offshore wind expansion scenarios for the German section of the North Sea with two distinct modelling approaches. This study presents the findings, and it underscores the importance of the role of the state in planning for a future with a lot more offshore wind energy.
Keywords: Windenergienutzung; Offshore-Anlage; Offshore-Windpark; Potenzialanalyse; Szenario; Energieerzeugung; Erneuerbare Energie; Energiewende; Klimaschutz